Impact of Virtual Clinics on Diabetes Distress and HbA1c Levels Among Patients with Diabetes Mellitus in Saudi Arabia - Mohammed A. Almarzooq; Hussain A. Almarzoug; Mohammed Jassim Alhassan; Mukhtar Ibrahim Alrashed; Jawad S. Alnajjar; Noor Abdullah Albejais; Suha Albahrani; Ibrahim A. Alibrahim; Abdullah Almaqhawi (Medicina)
Background and Objectives: Diabetes mellitus is a prevalent chronic disease caused by inadequate insulin secretion or ineffective insulin response, leading to complications such as retinopathy, nephropathy, heart attacks, and strokes. Recently, “diabetes distress (DD)” has emerged as a concept, highlighting the significant emotional burden of managing diabetes, which can impact disease outcomes. Thus, this study evaluates the impact of virtual clinics on diabetes distress and glycemic measures in individuals with diabetes mellitus. Materials and Methods: A cross-sectional study was conducted between May and August 2024 at the Endocrine and Diabetes Center in Alahsa, Saudi Arabia, targeting persons aged 18 and older with diabetes who had engaged in-person clinics, virtual clinics, or both between 2019 and 2024. Data were collected through structured phone interviews, supplemented by laboratory results from clinical records. The survey included demographic details, diabetes information, and the Diabetes Distress Scale. Statistical analyses, including descriptive statistics, were performed to explore the relationships between diabetes distress, clinic visit type, and glycemic control, with Mann–Whitney and Chi-Squared tests used to compare variables between two groups. Results: Of the 108 participants, 55.6% were male, with a mean age of 38.5 years. Type 2 diabetes was reported in 51.9% of individuals, while 48.1% had type 1. High emotional burden (44.4%) and regimen-related distress (28.7%) were prevalent, particularly among individuals with suboptimal glycemic control. While virtual visits were not significantly correlated with lower distress levels, individuals with suboptimal glycemic control exhibited significantly higher diabetes distress across various domains, including emotional and regimen-related distress (p < 0.05). Laboratory analysis showed a median HbA1c of 8.2%, with poor control associated with greater distress. Conclusions: Diabetic individuals with suboptimal glycemic control report higher diabetes distress levels, underscoring the need for integrated psychological support in DM care. Although virtual clinic visits did not significantly reduce distress, they provide a feasible option for individual follow-up.